Karakteristik Nugget Jamur Tiram Putih (Pleurotus ostreatus) dengan Penambahan Tepung Edamame (Glysin mac (L) Merrill) - Devianti, I Gusti Ayu Riza; Pratiwi, I Desak Putu Kartika; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Oyster mushroom nuggets are a favored plant-based nuggets which are popular because their taste is comparable to chicken meat. However, a weakness of white oyster mushroom nuggets is their lower protein content compared to chicken nuggets and has a soft texture caused by the high water content of white oyster mushrooms. Edamame flour is one type of high-protein plant-based ingredient. The addition of edamame flour to white oyster mushroom nuggets is expected to increase protein and improve texture. The goal of this study was to establish the features of white oyster mushroom nuggets with the addition of edamame flour, as well as the appropriate amount of edamame flour to generate the best white oyster mushroom nuggets. This study employed a totally randomised design with the inclusion of edamame flour at five levels: 0%, 5%, 10%, 15%, and 20%, which were repeated three times to provide 15 experimental units. The data obtained were analyzed by analysis of variance, and if there was a significant effect it would be followed by Duncan's multiple range test. The results showed that the addition of edamame flour had a significant effect (P<0.05) on water content, protein content, crude fiber content, texture tests including hardness, hedonic tests on color, aroma, taste, overall acceptability, and attribute intensity. sensory texture of white oyster mushroom nuggets. The addition of 10% edamame flour had the best characteristics of white oyster mushroom nuggets with the criteria of water content 45.62%, protein content 11.54%, crude fiber content 5.42%, hardness 1.28N, the texture is slightly chewy or slightly dense, color, aroma, taste, texture and overall acceptance are liked.